Analysis of Stress Contributing Factors in Work Organizations in Public Institutions of Higher Learning - Damin, Zahrul Akmal; Isa, Khairunesa; Jaes, Lutfan; Abdul Kadir , Zulida; Abdul Rahman, Abdul Halim (Journal of Social Transformation and Regional Development, 2021)
Stress is a condition that refers to the restless, anxious and tense situation a person faces due to stress or burden. This phenomenon of stress is increasingly serious in life including work organization. The problem of stress is increasingly focused because it can have negative implications for the organization such as decreased work productivity and high turnover rates as well as increasing the risk of accidents at work. Therefore, this paper aims to identify the factors that contribute to stress among staff in one of the Public Institutes of Higher Learning. The method used to achieve the objectives of this study is based on a quantitative approach by using simple random sampling techniques. A total of 535 respondents gave feedback through the distribution of questionnaires distributed. However, in the context of writing this article, only Part C involves open-ended questions regarding stress factors analyzed in a descriptive manner that includes numerical frequency and percentage. The results of the study found that the contributors to stress among staff are due to factors (i) organization; 429 frequency or 87.73%, (ii) individuals; 47 frequency or 9.61%, and (iii) family; 13 frequency or 2.66%. Matters related to stress are important to study because through the identification of factors contributing to stress among staff, then intervention measures can be designed to increase work motivation. By implementing such an approach, it is hoped that the work organization will continue to be competitive and have the strength to achieve the work targets that have been set.